Repeated phosphate removal from recirculating aquaculture system using cyanobacterium remediation and chitosan flocculation. (24th August 2017) - Rojsitthisak, Pranee; Burut‐Archanai, Surachet; Pothipongsa, Apiradee; Powtongsook, Sorawit
Abstract: Unicellular cyanobacterium Synechocystis sp. was used for phosphate removal in a recirculating aquaculture system. The cell harvesting was performed using chitosan solution in this study. The parameters (i.e. cell density, pH of cell suspension and chitosan concentration) affecting the flocculation efficiency of chitosan were investigated. With the optimal condition, the repeated flocculation for phosphate removal in a photobioreactor was demonstrated. The results show that the flocculation efficiency of chitosan depends on cell density, pH of cell suspension and chitosan concentration. The optimal flocculation process could be accomplished by adjusting the pH to 7.2 before adding 20 mg/L chitosan followed by pH adjustment to 7.5. With single inoculation, the sequential process of phosphate removal using cyanobacterial uptake followed by cell flocculation using chitosan with the optimal condition in the photobioreactor was successfully achieved for 12 cycles with water from a recirculating fish tank.